Strategi Guru dalam Mengembangkan Kecerdasan Eksistensial Anak di TK Terpadu Cinta Bunda Batubara - Mariani; Mhd. Habibu Rahman (Medan Resource Center, 2025)
This study aims to describe teacher strategies for developing existential intelligence in early childhood at the Cinta Bunda Batubara Integrated Kindergarten. Existential intelligence is a child's ability to understand the meaning of life, the purpose of existence, and their relationship with God and others. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that teachers implemented various strategies such as reflective activities, integrating spiritual values into learning, asking simple philosophical questions, using meaningful role-playing, and creating a religious and supportive classroom environment. These strategies have proven effective in stimulating children's self-awareness, fostering awareness of life values, and developing positive spiritual and emotional attitudes. These findings confirm the crucial role of teachers in guiding the development of existential intelligence in children from an early age through a planned and developmentally appropriate approach